2018
DOI: 10.1088/2053-1583/aad586
|View full text |Cite
|
Sign up to set email alerts
|

Excitons in few-layer hexagonal boron nitride: Davydov splitting and surface localization

Abstract: Hexagonal boron nitride (hBN) has been attracting great attention because of its strong excitonic effects. Taking into account few-layer systems, we investigate theoretically the effects of the number of layers on quasiparticle energies, absorption spectra, and excitonic states, placing particular focus on the Davydov splitting of the lowest bound excitons. We describe how the inter-layer interaction as well as the variation in electronic screening as a function of layer number N affects the electronic and opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
86
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(96 citation statements)
references
References 58 publications
(177 reference statements)
10
86
0
Order By: Relevance
“…This is in stark difference to the case with excitons at q→0 in bulk-hBN. At such condition, the doubly degenerate dark exciton house themselves in lower energy compared to the doubly degenerate bright excitons [10,12]. This degeneracy between bright and dark is removed at finite q where the later possess a very small oscillator strength [11].…”
Section: Resultsmentioning
confidence: 99%
“…This is in stark difference to the case with excitons at q→0 in bulk-hBN. At such condition, the doubly degenerate dark exciton house themselves in lower energy compared to the doubly degenerate bright excitons [10,12]. This degeneracy between bright and dark is removed at finite q where the later possess a very small oscillator strength [11].…”
Section: Resultsmentioning
confidence: 99%
“…This procedure is used to correct the usual quasiparticle gap underestimation given by the G 0 W 0 approximation [25] in BN systems. [26] We obtain a direct quasiparticle gap of 6.46 eV, and an indirect one of 5.96 eV ( Fig. 1a).…”
mentioning
confidence: 81%
“…In the following we will approximate the momentum difference of the indirect band gap as q = |K − M|. A discussion on this approximation with respect to the exact positions T 1 and T 2 [27] [28], we obtain two doubly degenerate excitonic states at q = 0 which form a Davydov pair [29,30] due to interlayer interaction [26]: The first exciton at 5.70 eV has E 2g symmetry and is thus dark. The second exciton at 5.75 eV (gray vertical line in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[28][29][30] ) on the electronic and optical properties of both the bulk and the single layer. These studies, supported by theoretical investigations, [31][32][33][34][35][36] have shown that h-BN is an indirect band gap insulator whose optical absorption spectrum is dominated by strongly bound excitons. Then, the electronic structures of the h-BN monolayer and of the bulk structure are fairly well known-which is convenient for the tight-binding model.…”
Section: A Choice Of the Systemmentioning
confidence: 81%